Power and decision making: new directions for research in the age of artificial intelligence. (June 2020) - Fast, Nathanael J; Schroeder, Juliana
Highlights: Power in social contexts shapes decision-making by facilitating goal-orientation. Power in social contexts guides decision-making via social role expectations. People may experience feelings of power when they interact with AI-based products. It is important to understand how AI-based power differs from human-based power. Abstract : Throughout history, the experience of power has occurred within the context of human–human interactions. Such power can influence decision making through at least two primary mechanisms: (1) increased goal-orientation, and (2) increased activation of social role expectations. Importantly, new advances in artificial intelligence (AI) are creating the potential to experience power in human–AI interactions. To the extent that some forms of AI can be made to seem like low-power humans (e.g. autonomous digital assistants), people may feel powerful when interacting with such entities. However, it is unclear whether feeling power over AI will lead to the same psychological consequences as feeling power over humans. In this article, we review findings on power and decision making and then consider how they may be meaningfully extended by considering interactions with artificially intelligent digital assistants. We conclude with a call for new theorizing and research on power in the age of artificial intelligence.